Investigating trainee instrumental/vocal teachers’ perceptions of dialogic teaching: an exploratory study - Poole, James; Norton, Naomi (Frontiers in Education, 2023)
This research explores perceptions of dialogic teaching amongst trainee instrumental/vocal teachers enrolled on the MA Music Education: Instrumental and Vocal Teaching programme at the University of York. 30 students from three different cohorts responded to an online questionnaire. Findings indicate that respondents were aware of a broader range of advantages of using dialogic teaching than disadvantages. Despite this, 59% of respondents reported that they inconsistently use dialogic teaching. Respondents also reported that they learn to use dialogic teaching through observation of fellow teachers, practical teaching experience, and peer-to-peer discussion. Some respondents viewed dialogic teaching primarily as a process of teacher-led questioning, rather than questioning and discussion, which suggests that trainee teachers may benefit from a more in-depth understanding of dialogic teaching within the context of instrumental/vocal lessons. The results of this research are of relevance to teachers, teacher educators, and providers of pedagogical resources.